CULTIVATION OF RELIGIOUS CHARACTER EDUCATION AT THE MEPEPADA CEREMONY AT PURA AGUNG KERTAJAYA TANGGERANG - Ni Nyoman Sudiani (UHN I Gusti Bagus Sugriwa Denpasar, 2024)
The yadnya ceremony is the basis of Hindu religious teachings, including tattva and ethics. Hindus implement religious teachings through the yadnya ceremony. There are five yadnya that are always carried out, namely Dewa Yadnya, Bhuta Yadnya, Manusa Yadnya, Pitra Yadnya and Rsi Yadnya. Interestingly, every Mupuk pedagingan ceremony is always accompanied by a mepepada ceremony, such as the Numpuk pedagingan ceremony at Pura Agung Kertajaya Tanggerang. This mepepada ceremony is interesting to study, especially in instilling character education values. The research method used is qualitative, data collection through interviews and observation. The results of the research show that there is an instillation of religious character education at the mepepada ceremony: belief in Lord Shiva in the form of Rare Anggon descending into the world to pick up the atman of the animal that is used as his yadnya, believing in the existence of the same atman for both animals and humans, believing that the good karma of the animal that is being used as his yadnya will receive purification and punarbhawa believes that the evolution of animals that are used as sacred sacrifices will be born into creatures that are better or more useful than before.